Reach Historical Thinking Skills: Developing Learning Models - Dimas Mahardika (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
The development of historical thinking skills is a significant accomplishment in achieving history learning objectives, and it requires special attention. To enhance these skills, students must practice historical research methods, which can support their historical thinking abilities. Through RnD, this study aims to improve students' historical thinking skills by creating innovative learning models. The research results indicate that the implementation of the developed product had a positive impact. The t-test post test of multiple choice questions in both classes showed a sig (2-tailed) level of 0.000, and the post test of historical thinking skills also showed a sig (2-tailed) level of 0.000. Both gains were below 0.05, indicating an average post-test difference in multiple choice and historical thinking skills in both classes. Based on the t-test results, we can conclude that the product positively affected the experimental class's learning outcomes and historical thinking skill